The implications of HIV infection on the management of valvular heart disease in Southern Africa - Naidoo, D.P.; Shein, K. (SA Heart Journal, 2017)
There is very limited information on the disease profile and treatment approaches in HIV patients with valvular heart disease (VHD) in developing countries. HIV infection impacts on patients with VHD in three settings: HIV/Aids as a comorbid disease in patients with underlying valve disease, infective endocarditis secondary to immunosuppression, and non-infective valve involvement from myocardial failure or from marantic endocarditis. The clinical presentation of infective endocarditis does not differ between HIV and non-HIV patients, with the exception that intravenous drug abuse is a common cause in specific populations. While peri-operative mortality and morbidity is high in acute infective endocarditis, surgical interventions do not increase the postoperative risk for complications or death and should therefore not be withheld. There is also little evidence to suggest that HIV or antiretroviral drugs increase the rate of cardiac-related pregnancy complications or that pregnancy may alter the course of HIV infection. Since antiretroviral therapy has been associated with considerable improvement in clinical status prior to surgery, as well as in long term outcomes, all patients with valve disease in whom intervention is likely should undergo HIV testing and staging so that highly active antiretroviral treatment (HAART) may be instituted timeously. Conclusion: The high prevalence of HIV in our population makes consideration of this comorbidity an essential facet in the routine evaluation and management of patients with VHD. There is solid evidence that these patients do no worse than non-HIV patients undergoing medical treatment or percutaneous/surgical intervention – open-heart surgery may be offered safely to patients with HIV if proper precautions are taken.